واقع تمكين المرأة في الجمهورية العربية السورية - الكردي, محمود فهمي; عديرة, محمود فاضل (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
شهدت سورية،كغيرها من دول العالم النامي،تطور الكثير من التغيرات السياسية والاقتصادية والاجتماعية التي أثرت في أوضاع النساء،حيث أدت تلك التحولات إلى نشوء أنماط جديدة من العلاقات الاجتماعية المتعلقة بالمرأة، فقد شهدت حياة النساء تطوراً ملحوظا ًفي المجالات كافة، منذ العام 1970 بدأت قضايا تمكين المرأة وتطويرها تحتل المرتبة الأولى في أجندة الحكومة السورية وكأولوية من أولويات التنمية. ونتيجة للاهتمام الكبير والمتزايد من قبل الحكومة السورية بقضية تمكين المرأة، وزيادة انخراط المرأة السورية في جميع مجالات الحياة العامة، سيقوم هذا البحث بالكشف عن واقع تمكين المرأة السورية سياسياً واقتصادياً وصحياً. ويهدف هذا البحث إلى مقاربة واقع تمكين المرأة في الجمهورية العربية السورية، كما ويهدف إلى الكشف عن مجالات التمكين (السياسي، الاقتصادي، الصحي) للمرأة في الجمهورية العربية السورية. وتوصل البحث الحالي إلى نتائج عدّة منها: أنّ انخراط المرأة في قوة العمل مرتبط بدورها التقليدي أي في الأعمال الزراعية والخدمية، كما أنّ المرأة السورية تمكّنت من الوصول إلى أعلى المناصب في الدولة فقد شغلت منصب نائب رئيس الجمهورية، غير أنّ مساهمتها في الحكومة والمجالس المحلية منخفضة، بينما شهد المستوى الصحي للمرأة السورية تطوراً كبيراً ورعاية أوسع فقد انخفضت نسبة وفيات الأمهات والأطفال وارتفعت نسبة الإناث اللاتي ولدن تحت إشراف متخصصين. Like many other countries in the developing world, Syria has witnessed several political, economical, and social changes which have affected the status of women. These changes led to the emergence of new patterns of social relations related to women, and women's lives have remarkably improved in all fields. Since 1970, women's empowerment issues started to rank high in the Syrian government's agenda and as a development priority. The large and growing interest by the Syrian government towards issues of women empowerment as well as the increased involvement of Syrian women in all spheres of public life (politics, economics, and health) merit some analysis. This paper seeks to identify the reality of women's empowerment in the Syrian Arab Republic, and tries to detect areas of enabling (political, economic, and health) of women in Syria. This research comes up with several interesting results: the involvement of women in labor forces is linked to their traditional role in agricultural and service sectors. Moreover, the Syrian woman has managed to reach higher jobs in the state as for example the position of vice president; nevertheless, her contribution to government and local councils remained low. Health care level of the Syrian woman has also witnessed major progress, where mothers' and children's death percentage has dramatically decreased and the number of females who give birth under supervision of specialists has multiplied.